CELLULAR MECHANISM UNDERLYING EMBRYO-MATERNAL RELATIONSHIP IN INTRASPECIFIC AND INTERSPECIFIC PREGNANCY - widayati, Diah tri; Fukuta, Katsuhiro (Jurnal Kedokteran Hewan, 2012)
Mouse and vole embryos were transferred into pseudopregnant CD-1 and scid female mice. Cellular changes involved in the formation of decidua in the pregnant mouse uterus up to day 8 of pregnancy were examined by histological, electron microscopic, and histochemical techniques. On day 6 of pregnancy, the vole embryos were laid in interstitium of antimesometrial side of the uterus, as well as in intraspecific pregnancy. Compared with intraspesific pregnant mouse, blood vessels were numerous in the decidua around the vole embryos in interspecific pregnancy. Both distribution and dilation of the blood vessels were increased on day 8. A part of cells in the inner cell mass had not nuclei, suggesting damaged vole embryos on day 8. At the implantation site, the uterine decidua was invaded by extravillous trophoblast (EVT) cells whose function is to destroy the walls of the uterine spiral. Moreover, this decidua was infiltrated by a population of natural killer (NK) cells and macrophage. These cells were particularly numerous in the decidua basalis at the implantation site where they come into close contact with invading EVT cells. These results suggest that interaction between NK, macrophage, and EVT provides the controlling relationship of embryo-maternal in intraspecific and interspecific pregnancy.